Painted Traces: Art and Ekphrasis in Elizabeth Kostova's The Swan Thieves. (November 2019) - Mitchell, Kate
Abstract : Nineteenth-century writers like Jane Austen, Mary Elizabeth Braddon, and Oscar Wilde were fascinated with the power of art. In their novels, the portrait could reveal secrets and capture the essence, or truth, of its subject. But how might painting be understood as a trace not of character so much as history? What power does the artwork have to connect us to past lives and histories today, continuing their activity into the present? Elizabeth Kostova's The Swan Thieves (2010) explores these questions by depicting artwork as talismanic, providing (a fantasy of) access to a past that is at once irretrievably lost and, potentially, available to imaginative reconstruction. As vestigial remains, the novel suggests, paintings manifest a past that is at once absent and present. The artwork it depicts exists within a complex set of relationships, including the narrative in which the paintings are embedded and which can only tell, and not show, the painting's power; the artist who paints and the viewer who beholds it, for whom the line between enchantment and enthrallment is easily blurred; and the past, whose relationship to the present the artwork both manifests and constructs. This article explores the use of art in this novel to reflect on the availability of the past in the present, as well as on neo-Victorianism itself, with its power to critique and rework the past and also to fascinate in the present. Ultimately, the novel captures not the power of art to access past lives, but a disconcerting vision of ourselves, caught in the act of (obsessive) re-representation.